Senyawa Metabolit Sekunder pada Daun Kelengkeng dan Daun Jeruk Limau yang Berkhasiat sebagai Obat Tradisional - Rifda Naufa Lina; Anggita Dipika Wulandari; Laelatul Husniyah (Pusat Riset dan Inovasi Nasional, 2025)
Public interest in natural remedies has increased significantly in recent years, leading to a growing reliance on traditional medicinal plants as alternative or complementary therapies. Among the plants widely used across generations in various cultural practices are longan leaves (Euphoria longan (Lour.) Steud) and kaffir lime leaves (Citrus amblycarpa (Hassk.) Ochse). Both are believed to possess a variety of health-promoting properties and have long been utilized in traditional medicine for their therapeutic potential. Despite their popularity, scientific investigations that specifically explore their phytochemical composition and pharmacological activities remain limited. This study was therefore conducted to examine the secondary metabolite content of both plants and to evaluate their potential as sources of bioactive compounds. The extraction process was carried out using the maceration technique with 96% ethanol as a solvent, followed by a series of phytochemical screening tests. The analysis aimed to identify the presence of key classes of secondary metabolites such as flavonoids, alkaloids, tannins, saponins, terpenoids, and steroids, which are known to contribute to various biological activities including antioxidant, anti-inflammatory, antimicrobial, and hepatoprotective effects. The results revealed that both longan and kaffir lime leaves tested positive for all targeted secondary metabolite groups. The consistent presence of flavonoids, alkaloids, tannins, saponins, terpenoids, and steroids suggests that these plants hold considerable pharmacological promise. Their metabolite profiles align with the reported therapeutic uses of these leaves in traditional medicine, providing scientific support for their continued application as herbal remedies. Overall, this research strengthens the understanding of Euphoria longan and Citrus amblycarpa as potential sources of phytopharmaceuticals. The findings not only validate their traditional medicinal uses but also highlight their potential in the development of natural-based drug formulations. Further in-depth studies, including isolation of active compounds and pharmacological assays, are recommended to fully characterize their therapeutic properties and clinical applications.